Analysis of drug management in Pharmacy Installations Colonel Abunjani Bangko Regional General Hospital - Maimum, Maimum (Journal of Pharmaceutical and Sciences, 2023)
Pharmaceutical care in the hospital is one activity that can support good quality. According to the previous observation, in some cases, the adding number of drugs, choosing a less precise drug, emptiness of the drug, and inexpediency between drug planning and consumption. Considering the importance of drug management, then it needs to be browsed all phases of drug management, from the beginning step of selection, procurement (planning and supplying), storage, distribution, and use. The study used descriptive analysis by taking prospective and retrospective data. Data related to drug management is analyzed to use indicator management of drugs. Then, the result is compared with existing standards and research done in another hospital. The results of the interview are also supported by further analysis. Study results indicate that the selection phase has not yet shown efficiency at indicator according to drug with DOEN and formularium. Phase of planning: did not make the drug requirement; on the other hand, the fund allocation is enough to make it. The phase of supplying: The frequency of providing drugs is low, and 15 35% of invoices do not match an order then, and delayed payment is 22 days on average. Storage and distribution show good results. The phase of use, the percentage of drugs prescribed by generic name for hospitalized and ongoing patients 27,1% and 32,3%, the rate of medicines prescribed from formulary for hospitalized 87, 78% and persistent patients 89,95%, percentage usage of antibiotics for hospitalized 12, 57% and 24, 82% for the ongoing patient, percentage usage of injection for hospitalized 47, 26%, the average number of drug per encounter 2, 9 for hospitalization and ongoing patient.